Emerging applications of gene editing technologies for the development of climate-resilient crops - Chavhan, R. L.; Jaybhaye, S. G.; Hinge, V. R.; Deshmukh, A. S.; Shaikh, U. S.; Jadhav, P. K.; Kadam, U. S.; Hong, J. C. (Frontiers in Genome Editing, 2025)
Climate change threatens global crop yield and food security due to rising temperatures, erratic rainfall, and increased abiotic stresses like drought, heat, and salinity. Gene editing technologies, including CRISPR/Cas9, base editors, and prime editors, offer precise tools for enhancing crop resilience. This review explores the mechanisms of these technologies and their applications in developing climate-resilient crops to address future challenges. While CRISPR/enables targeted modifications of plant DNA, the base editors allow for direct base conversion without inducing double-stranded breaks, and the prime editors enable precise insertions, deletions, and substitutions. By understanding and manipulating key regulator genes involved in stress responses, such as DREB, HSP, SOS, ERECTA, HsfA1, and NHX; crop tolerance can be enhanced against drought, heat, and salt stress. Gene editing can improve traits related to root development, water use efficiency, stress response pathways, heat shock response, photosynthesis, membrane stability, ion homeostasis, osmotic adjustment, and oxidative stress response. Advancements in gene editing technologies, integration with genomics, phenomics, artificial intelligence (AI)/machine learning (ML) hold great promise. However, challenges such as off-target effects, delivery methods, and regulatory barriers must be addressed. This review highlights the potential of gene editing to develop climate-resilient crops, contributing to food security and sustainable agriculture.